Rice SEPALLATA genes OsMADS5 and OsMADS34 cooperate to limit inflorescence branching by repressing the TERMINAL FLOWER1‐like gene RCN4 - Zhu, Wanwan; Yang, Liu; Wu, Di; Meng, Qingcai; Deng, Xiao; Huang, Guoqiang; Zhang, Jiao; Chen, Xiaofei; Ferrándiz, Cristina; Liang, Wanqi; Dreni, Ludovico; Zhang, Dabing (The New phytologist, 2022)
Summary The spatiotemporal control of meristem identity is critical for determining inflorescence architecture, and thus yield, of cereal plants. However, the precise mechanisms underlying inflorescence and spikelet meristem determinacy in cereals are still largely unclear. We have generated loss‐of‐function and overexpression mutants of the paralogous OsMADS5 and OsMADS34 genes in rice (Oryza sativa), and analysed their panicle phenotypes. Using chromatin immunoprecipitation, electrophoretic mobility‐shift and dual‐luciferase assays, we have also identified RICE CENTRORADIALIS 4 (RCN4), a TFL1‐like gene, as a direct downstream target of both OsMADS proteins, and have analysed RCN4 mutants. The osmads5 osmads34 mutant lines had significantly enhanced panicle branching with increased secondary, and even tertiary and quaternary, branches, compared to wild‐type (WT) and osmads34 plants. The osmads34 mutant phenotype could largely be rescued by also knocking out RCN4. Moreover, transgenic panicles overexpressing RCN4 had significantly increased branching, and initiated development of c. 7× more spikelets than WT. Our results reveal a role for OsMADS5 in panicle development, and show that OsMADS5 and OsMADS34 play similar functions in limiting branching and promoting the transition to spikelet meristem identity, in part by repressing RCN4 expression. These findings provide new insights to better understand the molecular regulation of rice inflorescence architecture.